Los juegos tradicionales y rescate de los valores culturales, en los niños de estimulación temprana, de la escuela dr. Daniel Rodas Bustamante - Astudillo Cuenca, Maricela Katherine (2018)
The theme of the present investigation is "TRADITIONAL GAMES AND RESCUE OF CULTURAL VALUES, IN CHILDREN OF EARLY STIMULATION, OF THE SCHOOL DR. DANIEL RODAS BUSTAMANTE ". The problem in the research process was the ignorance of traditional games does not allow to develop the cultural values of children of early stimulation in the school Dr. Daniel Rodas Bustamante. Whose general objective is to determine if the rescue of the traditional games allows to develop the cultural values in the children of early stimulation of the school Dr. Daniel Rodas Bustamante. For the development of the research the following methods were applied: Methods of the Theoretical Level: Analytical-Synthetic, Historical-Logical, Bibliographical Analysis; Empirical level methods: Observation, Percentage analysis, Analysis of results. Techniques and Instruments were the survey, test. Finally we obtained clear and precise results among the most important we have the test that was applied to the children of the aforementioned school, who told me that through traditional games it was possible to observe 100% of the cultural values. This allowed us to reach the following conclusion: The inclusion of traditional games as part of the study of physical culture, not only favors rescuing customs and traditions in children, but also promotes cultural values in them. And as a recommendation: Include traditional games in physical culture schedules in order that children develop their ability to interact with their peers and generate values that complement their education.